Two dimensional echocardiography and the tricuspid valve. Leaflet definition and prolapse. Issue 5 (May 1983) - Brown, A K; Anderson, V
Abstract : The tricuspid valve was studied in 143 subjects using two dimensional echocardiography. The groups studied were 40 normal subjects, 31 patients with mitral valve prolapse, 22 with clinically probable tricuspid valve prolapse, 20 with congestive cardiac failure, and 30 with miscellaneous cardiac conditions but no features of right heart disease. Using multiple views it was possible to record all three leaflets in 74.8% of cases and anterior and septal leaflets in 95%. Prolapse of the tricuspid valve was recognised in 13 patients: six (19.5%) of the group with mitral valve prolapse and seven (6%) of the remaining patients. Prolapse of all three leaflets was shown in one patient, anterior and septal prolapse in six patients, anterior and posterior in three patients, septal leaflet prolapse alone in two patients, and anterior alone in one patient. Two dimensional echocardiography allows definition of individual tricuspid leaflets and prolapse of any or all leaflets can be diagnosed. Tricuspid valve prolapse is commonly associated with prolapse of mitral valve leaflets but isolated cases are recognised.